Penentuan Kurva Pertumbuhan dan Aktivitas Antibakteri dari Isolat Ekstrak Etil Asetat Bakteri (Te.325) terhadap Staphylococcus aureus dan Escherichia coli - Alfian Syarifuddin; Ratna Wijayatri; Ichsan Feri Kurniawan; Herma Fanani Agusta (Fakultas Farmasi Universitas Pancasila, 2022)
The development of infection cases and inappropriate use of antibiotics has led to cases of antibiotic resistance. An alternative to overcoming the many antibiotics that are already resistant to bacteria has led to the discovery of new antibiotics. One of the processes of discovering antibiotics is from microorganisms, namely bacteria. The exploration process for the discovery of antibiotics uses a bacterial growth phase approach, namely the stationary phase which produces secondary metabolites, one of, which are bacteria that contain antibiotic compounds. Te.325 isolate is a producer of bacterial antibiotics but The growth phase is not yet known and can be used to approach the process of obtaining antibiotics. The study was to obtain the growth phase time of the Te.325 isolate and to extract antibiotic compounds from the isolate. The determination of the growth curve is based on the weight of cell biomass and the absorbance value on UV/ Vis spectrophotometry of the culture sampled every day for 14 days of culture incubation. The results showed a log/exponential phase on 5th day and a stationary phase on 9th day. The activity test of the ethyl acetate extract was carried out using the well method with an extract concentration of 40%, which resulted in an average diameter of 8.04mm in Staphylococcus aureus and 9.035mm in Escherichia coli. The ethyl acetate extract of Te.325 has medium potency.